On the Arrhenius-like behavior of conductivity during flash sintering of 3 mol% yttria stabilized zirconia ceramics. (October 2021) - Campos, João V.; Lavagnini, Isabela R.; Avila, Viviana; Yoon, Bola; Ghose, Sanjit; Raj, Rishi; Pallone, Eliria M.J.A.; Jesus, Lilian M.
Abstract: We discuss the Arrhenius behavior of electrical conductivity σ during flash sintering of 3 mol% yttria stabilized zirconia (3YSZ). In situ x-ray diffraction is used to determine sample temperature. Sintering contribution to σ is excluded by investigating the flash event on a dense ceramic. We show that total conductivity follows an Arrhenius-like equation in both dense and green samples, even during Stage II of flash. The non-linearity often verified during flash sintering of 3YSZ is therefore related to the furnace temperature instead of the sample temperature when building the ln( σ ) vs. 1/T plots. Furthermore, we verified a change in the activation energy for conduction prior to the ignition of the flash event and discussed the possible mechanisms. For instance, the decrease in activation energy from Stage I to II in the dense sample is attributed to a contribution from electronic carriers. Graphical abstract: Image, graphical abstract